Neuroprotective Potential of Origanum majorana L. Essential Oil Against Scopolamine-Induced Memory Deficits and Oxidative Stress in a Zebrafish Model - Ion Brinza; Razvan Stefan Boiangiu; Iasmina Honceriu; Ahmed M. Abd-Alkhalek; Samir M. Osman; Omayma A. Eldahshan; Elena Todirascu-Ciornea; Gabriela Dumitru; Lucian Hritcu (Biomolecules)
Origanum majorana L., also known as sweet marjoram, is a plant with multiple uses, both in the culinary field and traditional medicine, because of its major antioxidant, anti-inflammatory, antimicrobial, and digestive properties. In this research, we focused on the effects of O. majorana essential oil (OmEO, at concentrations of 25, 150, and 300 μL/L), evaluating chemical structure as well as its impact on cognitive performance and oxidative stress, in both naive zebrafish (Danio rerio), as well as in a scopolamine-induced amnesic model (SCOP, 100 μM). The fish behavior was analyzed in a novel tank-diving test (NTT), a Y-maze test, and a novel object recognition (NOR) test. We also investigated acetylcholinesterase (AChE) activity and the brain’s oxidative stress status. In parallel, we performed in silico predictions (research conducted using computational models) of the pharmacokinetic properties of the main compounds identified in OmEO, using platforms such as SwissADME, pKCSM, ADMETlab 2.0, and ProTox-II. The results revealed that the major compounds were trans-sabinene hydrate (36.11%), terpinen-4-ol (17.97%), linalyl acetate (9.18%), caryophyllene oxide (8.25%), and α-terpineol (6.17%). OmEO can enhance memory through AChE inhibition, reduce SCOP-induced anxiety by increasing the time spent in the top zone in the NTT, and significantly reduce oxidative stress markers. These findings underscore the potential of using O. majorana to improve memory impairment and reduce oxidative stress associated with cognitive disorders, including Alzheimer’s disease (AD).